2010
DOI: 10.1177/0093854810372898
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe Mental Illness On Parole Decisions

Abstract: This study examined the extent to which severe mental illness (SMI) affects parole release decisions either directly or indirectly through its association with other factors considered in the parole release decision-making process. A random sample of 407 inmates with parole release decisions in 2007 (200 with SMI and 207 without SMI) was selected from the New Jersey State Parole Board. Data on inmates’ program participation, misconduct, and job assignments while incarcerated along with levels of community supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 103 publications
(123 reference statements)
2
24
0
Order By: Relevance
“…In this study, we relied on a general measure of prior convictions (measure often employed in studies of recidivism). Following other parole decision-making research [56,63,64,70,76,77], the study also controlled for time served (length of incarceration from commitment to parole interview date). More recent research [58,80] also indicates that prior parole reviews and visitation of inmates while in prison may also influence the likelihood of a candidate’s gaining release; thus, the current analyses also controlled for these two factors (binary measures for both).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we relied on a general measure of prior convictions (measure often employed in studies of recidivism). Following other parole decision-making research [56,63,64,70,76,77], the study also controlled for time served (length of incarceration from commitment to parole interview date). More recent research [58,80] also indicates that prior parole reviews and visitation of inmates while in prison may also influence the likelihood of a candidate’s gaining release; thus, the current analyses also controlled for these two factors (binary measures for both).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to mental health and its impact on parole, the research is limited, and findings have been inconsistent; some studies found inmates with mental health problems are less likely to be paroled than nonmentally ill inmates [68,69], while others that mental health issues do not appear to impact parole decision making [70,71]. Caplan [56] (2007) conducted a review of the existing literature and found mental health status to have a negative impact on parole decisions and also to be one of the main influential factors on parole decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The current study utilized previously collected data for an investigation of the relationship between severe MI and parole release decisions (Matejkowski, Caplan, & Cullen, 2010). The sampling frame was extracted from the New Jersey State Parole Board's Information System (PBIS).…”
Section: Sampling Strategymentioning
confidence: 99%
“…Education may be an indicator of pre-confinement stability or community support (Cunningham & Sorensen, 2006; Feder, 1994); alternatively, it can be an indicator of rehabilitation if an inmate participated in education programs during imprisonment. Conversely, mentally ill prisoners are more likely to be charged with rule violations and receive disciplinary actions (James & Glaze, 2006; Matejkowski, Caplan, & Cullen 2010; O’Keefe, 2007). A study with a nationally representative sample of over 16,000 inmates found psychosis, depression, and paranoia were associated with both violent and nonviolent infractions while controlling for potential confounders such as prior violence and substance use (Felson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%